Public Awareness on the Rationale Consumption and Appropriate Disposal Methods of Unused and Expired Medications in Kanchipuram District, Tamilnadu, India - Rajaraman, Hema Gowtham; Panneerselvam, Nithya; Shanmugam, Hemanthkumar; Gupta, Madhu (Scripta Medica, 2024)
Background/Aim: Improper drug disposal methods are a threat to the nature and its ecosystem by accumulation of active compounds included in these pharmaceuticals. Aim of this study was to assess the knowledge, attitude and practice (KAP) on the rationale consumption and appropriate disposal methods of unused and expired medications among common public in Kanchipuram district, Tamilnadu, India. Method: KAP questionnaire was prepared to get responses from all participants who had volunteered for the study. Questionnaire had queries pertaining to the personal information about the respondent and respondent’s knowledge, practice and attitude concerning drug usage, the disposal methods of unused and expired medicines and their awareness and knowledge towards drug take back program.Results: In this study 37.91 % out of the 807 participants had excellent knowledge on the rationale consumption and appropriate disposal of unused/expired medications, 48.94 % had average knowledge, but only 6.56 % of the total participants had more positive attitude and 66.66 % had positive attitude. Only around 45.84 % of the participants were following the good practices.  Conclusion: Guidelines, policies and strict vigilant actions need to be initiated by government of India for safe utilisation of pharmaceutical products and disposal of unused/expired medications to safeguard our ecosystem from some of the major treats like antimicrobial resistance.